An Overview of Psychological Responses to Armed Conflict and Rural Banditry in Zamfara State - Yalwa, Tasi'u; Shehu, Ado; Balarabe, Fatima; Musa, Zulkiflu; Abdullahi, Nasir Muhammed; Ayuba, Attahir Sa’ad; Hayat, Gomma; Jibreel, Ebtesam (Universitas Airlangga, 2025)
Introduction: Armed conflict in Nigeria, particularly in Zamfara State, has resulted in numerous casualties, kidnappings, deaths, torture, rape, and destruction of property. This violence has been strongly associated with the development of mental health disorders such as post-traumatic stress disorder (PTSD), depression, anxiety disorders, and substance use disorders, especially in resource-limited settings like Zamfara. This study aimed to assess the mental health and psychological implications of armed conflict among survivors of rural banditry in Zamfara State. Method : A cross-sectional descriptive survey design was employed, involving 410 participants aged 11 years and above, selected through multistage and simple random sampling techniques. Data were collected using the General Health Questionnaire (GHQ-12) and analysed using descriptive statistics with SPSS version 26.0. Results : The findings revealed that the majority of respondents experienced mild psychological symptoms (mean score 1.75), while a smaller proportion exhibited moderate symptoms (mean score 2.25 to ≤3). Additionally, some participants reported severe symptoms of anxiety, depression, and post-traumatic stress disorder (PTSD). Conclusions : The study concludes that a significant proportion of survivors of rural banditry in Zamfara State experience varying degrees of psychological distress. Based on these findings, the study recommends urgent interventions and support for mental health in the region, including the provision of mental health services, psychological interventions, community support programs, capacity building, and continuous research and monitoring. Introduction: Armed conflict in Nigeria, particularly in Zamfara State, has resulted in numerous casualties, kidnappings, deaths, torture, rape, and destruction of property. This violence has been strongly associated with the development of mental health disorders such as post-traumatic stress disorder (PTSD), depression, anxiety disorders, and substance use disorders, especially in resource-limited settings like Zamfara. This study aimed to assess the mental health and psychological implications of armed conflict among survivors of rural banditry in Zamfara State. Method : A cross-sectional descriptive survey design was employed, involving 410 participants aged 11 years and above, selected through multistage and simple random sampling techniques. Data were collected using the General Health Questionnaire (GHQ-12) and analysed using descriptive statistics with SPSS version 26.0. Results : The findings revealed that the majority of respondents experienced mild psychological symptoms (mean score 1.75), while a smaller proportion exhibited moderate symptoms (mean score 2.25 to ≤3). Additionally, some participants reported severe symptoms of anxiety, depression, and post-traumatic stress disorder (PTSD). Conclusions : The study concludes that a significant proportion of survivors of rural banditry in Zamfara State experience varying degrees of psychological distress. Based on these findings, the study recommends urgent interventions and support for mental health in the region, including the provision of mental health services, psychological interventions, community support programs, capacity building, and continuous research and monitoring.